Implementasi Problem Based Learning dalam Pembelajaran Iman kepada Malaikat untuk Meningkatkan Partisipasi Siswa di Kelas VII-3 SMPN 2 Lubuk Sikaping - Putra, Roli Kardinal (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to explore effective methods for improving students’ understanding of Pancasila. Based on data analysis, it can be concluded that the implementation of the StudentCentered Learning (SCL) method yields more significant results in enhancing learning outcomes compared to the conventional method. Students taught using the SCL approach are more actively involved in the learning process, more motivated, and show greater improvement in understanding the concepts of Pancasila. In contrast, while the conventional method remains effective in teaching the fundamentals of Pancasila, the lack of active interaction and opportunities for personal exploration diminishes students’ deeper understanding. This study recommends the use of SCL as a more suitable method to facilitate deeper and participatory learning in the context of Pancasila education.